Fungal flocculants to reduce turbidity of river water - Jebun, N.; Al Mamun, Abdullah; Alam, Md Zahangir; Ahmad Raus, Raha (Asian Research Publishing Network (ARPN), 2016)
River water contains both dissolved and suspended particles. Coagulation and flocculation processes are used to separate the suspended solids from the water. Conventionally, suspended solids and turbidity are removed from raw water by various chemical coagulants but most of them are costly and non-ecofriendly. Whereas, the bioflocculants are environment-friendly and could be used as coagulants. In general, bioflocculants cause aggregation of particles and cells by bridging and charge neutralizing. Most of the solids suspended in water possess negative charges and repel each other, for which they do not settle in the water body. This present study attempted to reduce turbidity of river water and kaolin suspension using fungal coagulants in Jar apparatus. Bioflocculant producing filamentous fungi were isolated from river water. Si strains showed good flocculating performance. Among them, supernatant of RWF-05 and RWF-06 showed turbidity removal of 95% and 75% from kaolin suspension, respectively. However, the removal of turbidity from river water was rather low with 23% and 22%, respectively. Dried biomass of RWF-03 showed a good flocculating rate of 80% after 24h settling time to kaolin suspension. The results showed that the clay particles of river water and kaolin were flocculated by the fungal supernatant and dried biomass and, as a result, they reduced the turbidity of river water.